Prenatal exposure to persistent organochlorine pollutants and female reproductive function in young adulthood. (July 2016) - Kristensen, Susanne Lund; Ramlau-Hansen, Cecilia Høst; Ernst, Erik; Olsen, Sjurdur Frodi; Bonde, Jens Peter; Vested, Anne; Halldorsson, Thorhallur Ingi; Rantakokko, Panu; Kiviranta, Hannu; Toft, Gunnar
Abstract: Background: The biopersistent organochlorine pollutants dichlorodiphenyldichloroethylene (p, p′-DDE), hexachlorobenzene (HCB) and polychlorinated biphenyls (PCBs) can be detected in humans worldwide. The chemicals can cross the placenta and may interfere with endogenous hormonal homeostasis. Objectives: To investigate effects on female reproduction following intrauterine exposure to selected biopersistent organochlorines. Methods: We used data from a Danish pregnancy cohort with follow-up on 436 eligible daughters at approximately 20 years of age. Information on age of menarche ( n = 335), menstrual cycle length ( n = 230) and serum concentrations of reproductive hormones ( n = 243) was obtained. Number of antral follicles was counted by vaginal ultrasound ( n = 147). Of 244 daughters who attended clinical examination, 170 used hormonal contraceptives and 74 were non-users. Concentrations of p, p′-DDE, HCB and six PCB congeners were analysed in maternal serum samples obtained in pregnancy week 30. Results: Age of menarche and menstrual cycle length were found not to be statistically significant associated with prenatal organochlorine exposure. Among non-users of hormonal contraceptives with information on antral follicle number ( n = 43), daughters exposed to the highest tertile of p, p′-DDE had 28% (95% confidence interval (95% CI): 5; 46%) lower follicle number compared to the low-level exposed reference group. Those exposed to medium and higher levels of HCB had 30% (95% CI: 5; 48%) and 28% (95% CI: 7; 44%) lower follicle number compared to the reference group. Furthermore, maternal serum HCB concentrations were inversely associated with free androgen index among non-users of hormonal contraceptives ( n = 73). These associations were not found in users of hormonal contraceptives. Conclusions: Among non-users of hormonal contraceptives, we found indications of adverse long-term effects on female reproduction following prenatal exposure to biopersistent organochlorines. These findings may have wide implications for public health as intrauterine exposure occurs worldwide. Highlights: Biopersistent organochlorine pollutants may affect human intrauterine development. Fetal exposure to organochlorines was related to reproductive function in adulthood. Higher DDE and HCB levels were associated with lower number of ovarian follicles. Higher HCB exposure was related to lower levels of androgens. This indicates long-term effects on human female reproductive function